2-Methyl-3′-(4-methylphenyl)-4′-(2-nitrophenyl)-4′H-spiro[chroman-3,5′-isoxazol]-4-one - Asmae Mahfoud; Ghali Al Houari; Mohamed El Yazidi; Mohamed Saadi; Lahcen El Ammari (IUCrData, 2018)
The title compound, C25H20N2O5, crystallizes with two molecules (A and B) in the asymmetric unit with similar conformations. The five-membered rings are both in envelope conformations with the spiro C atom as the flap. The six-membered heterocycles display half-chair conformations. The mean plane through the isoxazole ring is nearly perpendicular to those through the spiro-chroman system and the 4-nitrophenyl moieties, as indicated by the dihedral angles of 81.42 (9) and 87.58 (8)°, respectively, between them in molecule A. Equivalent data for molecule B are 75.58 (9) and 84.15 (8)°, respectively. The p-tolyl plane makes a dihedral angles of 24.10 (9) and 28.78 (8)° with the isoxazole ring in molecules A and B, respectively. In the crystal, molecules are linked by C—H...O and C—H...N hydrogen bonds and C—H...π interaction, forming a three-dimensional network.